Engaging postgraduate students with business through design thinking experiential workshops - Withell, AJ; Reay, S (Hong Kong Design Centre, 2011)
It is essential that design education extends beyond the classroom to ensure that students are fully prepared to engage with other disciplines, such as business. Design Thinking has emerged as a key mechanism to engage design with business, and vice versa. This paper describes how the Product Design department at AUT University has identified an opportunity to educate businesses and organisations about the principles, processes and methods of Design Thinking, and maximising the learning educational benefits of this situation, to engage postgraduate students with business perspectives and contexts. Consequently, Design Thinking Participatory Workshops for business were proposed and tested. This paper specifically outlines the background and the theoretical perspectives behind the workshops, as well as describing the current business context of New Zealand. In particular the paper describes how the application of Design Thinking is assisting in the transformation of a number of leading New Zealand businesses and organisations. It then discusses the design and development of the prototype Design Thinking workshops, including the approach used, the two day structure, the role of postgraduate students, and materials presented. The paper then presents the results of one the workshops run to date, including an evaluation from student and industry perspectives.